6th Conference on Automated Deduction
DOI: 10.1007/bfb0000061
|View full text |Cite
|
Sign up to set email alerts
|

Deciding combinations of theories

Abstract: Abstract. A method ~s g~ven for dec~dlng formulas in combinations of unquantified first-order theories. Rather than couphng separate decision procedures for the contributing theories, the method makes use of a single, uniform procedure that minimizes the code needed to accommodate each additional theory. It ~s apphcable to theories whose semantics can be encoded within a certain class of purely equational canonical form theories that ~s closed under combination. Examples are given from the equational theories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 8 publications
0
90
0
Order By: Relevance
“…Nelson and Oppen's method [NO79] combines decision procedures for the individual theories by allowing them to share specific kinds of equality information. Shostak's method [Sho84] extends congruence closure to equational theories that are canonizable and solvable. Nelson and Oppen's method is more generally applicable, but Shostak's method has certain advantages.…”
Section: Shostak's Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Nelson and Oppen's method [NO79] combines decision procedures for the individual theories by allowing them to share specific kinds of equality information. Shostak's method [Sho84] extends congruence closure to equational theories that are canonizable and solvable. Nelson and Oppen's method is more generally applicable, but Shostak's method has certain advantages.…”
Section: Shostak's Algorithmmentioning
confidence: 99%
“…We present here the first instance of a verified decision procedure for a combination of theories based on Shostak's ideas. Shostak's algorithm [Sho84] for building decision procedures for the union of canonizable and solvable equational theories has been widely used despite the lack of a convincing correctness proof. Recently, Ruess and Shankar [RS01] showed that this algorithm (even with minor flaws corrected [CLS96]) was both nonterminating and incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Work on theorem proving has focused on decomposition for parallel implementations [8,5,15,43] and has followed decomposition methods guided by lookahead and subgoals, neglecting the types of structural properties we used here. Another related line of work focuses on combining logical systems (e.g., [32,40,3,36,44]). Contrasted with this work, we focus on interactions between theories with overlapping signatures, the efficiency of reasoning, and automatic decomposition.…”
Section: Related Workmentioning
confidence: 99%
“…SVC is a decision procedure for quantifier-free first-order logic and uses an algorithm similar to the algorithms by Shostak [20,19] and Nelson-Oppen [17]. The input Boolean formula to SVC can contain Boolean operators, uninterpreted functions and interpreted functions, and distinct constants such as the Boolean truth and bit constants.…”
Section: (P! Ai(s)) ^ I(si)mentioning
confidence: 99%